Histopathologic Distribution of Appendicitis at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, in 2012 - Tara Zhafira; Herry Yulianti; Maman Wastaman (Althea Medical Journal, 2017)
Background: Appendicitis is a medical emergency and a common cause of emergency surgeries worldwide. Its frequency is varied based on many factors, including age and sex. Histopathologic examination is a gold standard for diagnosis, and complications like gangrene formation and perforation lead to high mortality and morbidity in almost all age groups. This study was conducted to describe the distribution pattern of appendicitis according to age, sex, and histopathologic type. Methods: This cross-sectional study was carried out in the Department of Pathology Anatomy, Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, from August–October 2013. Secondary data were obtained from medical records of January 1st to December 31st, 2012. A total of 503 out of 516 cases were included to be reviewed. Age, sex, and histopathologic type from medical records were then evaluated. Any specific case and perforation were also noted.Results: Data showed the highest prevalence of appendicitis occurred in the 10- 19 age group (28.4%) and in the female group (52.3%). Acute appendicitis was more common than chronic appendicitis in both sexes and all age groups. Perforation rate was high (41.4%), and was more prevalent in male (54.9%) and in the 0–9 age group (65.7%).Conclusions: Appendicitis, both acute and chronic, is more distributed in the second decade, and is slightly more prevalent in females. Acute cases are more common than chronic. Perforation rate is significant and peaks in the first decade and in males. [AMJ.2017;4(1):36–41]DOI: 10.15850/amj.v4n1.1017